Three-Dimensional Anthropometric Analysis of the Effect of Lip Reconstructive Surgery on Children with Cleft Lip and Palate at Three Different Times - Gabriela Mendonça Rando; Eloá Cristina Passucci Ambrosio; Paula Karine Jorge; Chiarella Sforza; Márcio Menezes; Ana Lúcia Pompeia Fraga de Almeida; Simone Soares; Gisele Silva Dalben; Cristiano Tonello; Cleide Felício Carvalho Carrara; Maria Aparecida Andrade Moreira Machado; Thais Marchini Oliveira (MDPI AG, 2024)
Objectives: This investigation aimed to assess the optimal timing for lip repair in children with cleft lip and palate via 3D anthropometric analysis to evaluate their maxillofacial structures. Methods: The sample comprised 252 digitized dental models, divided into groups according to the following timing of lip repair: G1 (n = 50): 3 months; G2 (n = 50): 5 and 6 months; G3 (n = 26): 8 and 10 months. Models were evaluated at two-time points: T1: before lip repair; T2: at 5 years of age. Linear measurements, area, and Atack index were analyzed. Results: At T1, the intergroup analysis revealed that G1 had statistically significant lower means of I-C', I-C, C-C', and the sum of the segment areas compared to G2 (p = 0.0140, p = 0.0082, p = 0.0004, p < 0.0001, respectively). In addition, there was a statistically significant difference when comparing the cleft area between G2 and G3 (p = 0.0346). At T2, the intergroup analysis revealed that G1 presented a statistically significant mean I-C' compared to G3 (p = 0.0461). In the I-CC' length analysis, G1 and G3 showed higher means when compared to G2 (p = 0.0039). The I-T' measurement was statistically higher in G1 than in G2 (p = 0.0251). In the intergroup growth rate analysis, G1 and G2 showed statistically significant differences in the I-C' measurement compared to G3 (p = 0.0003). In the analysis of the Atack index, there was a statistically significant difference between G1 and the other sample sets (p < 0.0001). Conclusion: Children who underwent surgery later showed better results in terms of the growth and development of the dental arches.